A netnographical approach to typologizing customer engagement and corporate misconduct. (March 2021) - Hua, Lian-Lian; Prentice, Catherine; Han, Xiaoyun
Abstract: Customer engagement has important implications for the organization. The study developed a typology to understand customer engagement and its relationship with corporate misconduct. Customer engagement is categorized into co-developing, augmenting, influencing, and mobilizing behaviors, which are typologized into organizational and peer engagement, with co-developing and augmenting behaviors classified as organizational engagement, and the remaining two as peer engagement. In view of a focus on negative engagement in the case of corporate misconduct in previous research, this study deployed a netnographical approach to exploring positive and neutral engagement within the organization and with peers. The findings indicate that corporate misconduct not only elicits a negative response but may also elicit positive or indifferent engagement behaviors. This study contributes to customer engagement and corporate misconduct research by delving into underexplored aspects of consumer behavior.